الاجتهاد والإفتاء وتطوره المؤسساتي المعاصر: المفهوم، المقومات، والإجراءات العامة: The Deveopment of Ijtihād and Iftāʿ in the Contemporary Institutional Landscape: Concepts, Foundations, and General Procedures - Hamza Khelifati; Bouhedda; Mohamad Sabri B Zakaria (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يهدف هذا البحث إلى دراسة المؤسسة كمظهر من مظاهر تطور الاجتهاد والإفتاء في هذا العصر من خلال تحديد مفهوم الاجتهاد المؤسساتي وإبراز أهم مقوماته، وبيان الفرق بينه وبين الاجتهاد الفردي والجماعي، والتطرق إلى المراحل التاريخية التي مرّ بها، وبيان آليات عمله وإجراءاته العامة. تتجلى أهمية هذا البحث في أن الاجتهاد والإفتاء في النوازل والمستجدات لم يعد مقتصرًا على الجهود الفردية، بل أصبح عملًا مؤسساتيًا يعتمد على تضافر جهود الأفراد من مختلف التخصصات والمعارف. يحاول البحث معالجة قصور الاجتهاد الفردي في واقعنا المعاصر من خلال بيان وتحديد المقومات التي تجعل الاجتهاد المؤسسي أكثر فعالية من الاجتهاد الفردي في مواجهة تحديات العصر الحديث، وكيف تسهم هذه المقومات في تعزيز القدرة على تحقيق أهداف الاجتهاد ومقاصده. اعتمد البحث على المنهج الوصفي التحليلي؛ حيث ركّز الجانب الوصفي على تتبع وجمع المادة البحثية، والجانب التحليلي على دراسة المفاهيم والتصورات الرئيسية للموضوع، ودراسة تاريخ ظهور نشأة الاجتهاد والإفتاء المؤسساتي، وتحليل إجراءات عمل مؤسساته. وقد خلص البحث إلى جملة من النتائج، من أبرزها أن الاجتهاد المؤسساتي يوفر إطارًا أكثر شمولية ودقة لمعالجة القضايا المعاصرة، كما يسهم في تعزيز مصداقية الفتاوى لدى الجمهور ويزيد من قبولها. توصي الدراسة بتطوير آليات العمل الجماعي المؤسساتي في الاجتهاد والإفتاء وتوفير الدعم اللازم لها. ABSTRACT This research aims to examine the institution as a manifestation of the development of Ijtihād and Iftāʿ in the contemporary era. It seeks to define the concept of institutional Ijtihād, highlight its key components, differentiate it from individual and collective Ijtihād, trace its historical stages, and outline its general mechanisms and procedures. The significance of this research lies in the fact that Ijtihād and Iftāʿ regarding emerging issues are no longer confined to individual efforts but have become an institutional endeavor that relies on the collaboration of individuals from various disciplines and fields of knowledge. The research attempts to address the shortcomings of individual Ijtihād in contemporary times by identifying and defining the elements that make institutional Ijtihād more effective than individual Ijtihād in facing the challenges of the modern age, and how these elements contribute to enhancing the ability to achieve the goals and objectives of Ijtihād. The research adopts a descriptive and analytical approach. The descriptive aspect focuses on tracing and collecting research material, while the analytical aspect examines the main concepts and perceptions of the topic, studies the history of the emergence of institutional Ijtihād and Iftaʿ, and analyzes the working procedures of its institutions. The research has reached a number of conclusions, most notably that institutional Ijtihād provides a more comprehensive and accurate framework for addressing contemporary issues, and contributes to enhancing the credibility and acceptance of fatwas among the public. The study recommends developing the mechanisms of institutional teamwork in Ijtihād and Iftāʿ and providing the necessary support for them.